Islamic Pedagogical Competencies for Sustainable Hospitality Education - Liting Zeng; Jiraporn Chano; Bahtiar Mohamad (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
Teaching competency is pivotal in advancing higher education, particularly in preparing students to address sustainability challenges in the hospitality sector. This study develops a comprehensive framework that integrates the Sustainable Hospitality Education (SHE) Teacher Competency Scale with UNESCO’s Education for Sustainable Development (ESD) competencies and the Islamic educational principles of tarbiyah (holistic nurturing), ta’dib (ethical formation), and ta’lim (knowledge cultivation). Employing a mixed-method design, qualitative data were gathered from semi-structured interviews with 20 academic experts, and quantitative data were collected from 304 undergraduate hospitality students. Thematic analysis and exploratory factor analysis (EFA) identified five key competency dimensions: Motivation and Values, Knowledge and Expertise, Pedagogical Competence, Sustainability Integration, and Collaborative Growth. The final 20-item scale demonstrated strong reliability and validity. The results highlight the significance of fostering educators’ ethical commitment, sustainability literacy, and collaborative engagement with industry stakeholders. For Islamic higher education institutions, the study provides a validated and context-sensitive framework for curriculum enhancement, professional development, and policy formulation. By aligning sustainability competencies with Islamic values of stewardship (khilafah) and social cooperation (ta’awun), the framework contributes to producing educators and graduates capable of leading transformative change toward a just and sustainable society.